2005
DOI: 10.1021/ma050362x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Chain Tilt on the Interaction between Brush-Coated Colloids

Abstract: The interaction between two spherical particles coated by end-grafted polymers immersed in a good solvent is examined using the strong-stretching theory of Milner, Witten, and Cates. Our calculation allows the polymer chains to tilt outward from the axis of closest approach, where the separation between the substrates is a minimum. This transfers the stress toward the extremity of the contact region, but to such a degree that the central chains can experience a reduction in free energy relative to the unpertur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 19 publications
1
24
0
Order By: Relevance
“…Indeed, this effect has been anticipated by molecular dynamics (MD) simulations of pairwise interactions between alkanethiol-capped Au NCs 34 and self-consistent field theory calculations of overlapping spherical brushes. 38 Capping ligand structure may also be influenced by the amorphous carbon film that supports 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 With simple geometry and chain packing assumptions, OPM and OCM are appealing models for considering "hairy" sphere packings. OPM correctly predicts the dimensions of extended NC arrays.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, this effect has been anticipated by molecular dynamics (MD) simulations of pairwise interactions between alkanethiol-capped Au NCs 34 and self-consistent field theory calculations of overlapping spherical brushes. 38 Capping ligand structure may also be influenced by the amorphous carbon film that supports 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 With simple geometry and chain packing assumptions, OPM and OCM are appealing models for considering "hairy" sphere packings. OPM correctly predicts the dimensions of extended NC arrays.…”
Section: Resultsmentioning
confidence: 99%
“…The most accurate approach 4,23 uses the free energy per chain, f(l; R), from a single particle of radius, R, with its brush compressed to a thickness of l. The Appendix provides a simple analytical estimate for f(l; R) calculated with SST. In SCFT, f(l; R) has to be evaluated numerically, but this is nevertheless a trivial one-dimensional calculation of an isolated particle with a reflecting boundary placed at r ) R + l. Once the free energy of the uniformly compressed brush is known, the interaction energy of nonuniform compression is approximated as…”
Section: Derjaguin Approximationmentioning
confidence: 99%
“…As expected, we find that the force between the two particles is purely repulsive regardless of the particle size, brush thickness, or particle separation. We also take advantage of our full SCFT solution to examine the accuracy of the former SST approach in ref 4 and to test the reliability of the Derjaguin approximation.…”
Section: Introductionmentioning
confidence: 99%
“…With these sophisticated theories, the effect of chain tilting during the interaction can also be taken into account. 25 Although these models provide useful insights into the phenomenon of steric interaction, the application of these models is limited by the fact that only numerical solutions of these models are available. Lozsan et al found that a model based on the Flory−Krigbaum theory assuming uniform segment density distribution (it was called extended Vincent (EV) model by the authors) could quantitatively describe the steric interaction between two spherical particles with satisfactory accuracy, 31 which indicates that simple mathematical descriptions are available to yield sufficient approximation for estimating the steric interaction energy.…”
Section: ■ Introductionmentioning
confidence: 99%